Densities of the Eurasian Threetoed Woodpecker Picoides tridactylus calculated from sap row surveys are on par with estimates from fixed route bird censusing - Ferry, Björn; Ekenstedt, Johan; Green, Martin (Ornis Svecica, 2021)
Species-specific tracks animals can be an effective way of mapping species that are hard to find even if they are present. We used observations of sap rows on trees to calculate densities of Eurasian Three-toed Woodpeckers Picoides tridactylus. We surveyed 14 fixed routes in northern Sweden below the montane forest for sap rows during the autumn of 2020. We used our observations of fresh sap rows together with average home range and proportion of active territories per year derived from the literature, to calculate large-scale woodpecker population density. The density based on sap rows was 0.19 pairs per km2. Densities from fixed route bird observations for different parts of Västerbotten County below the montane forests were 0.13–0.14 pairs per km2, in relative agreement with the estimates from sap rows. We also calculated the population density from fixed route observations in the montane forests, and these were almost three times higher. Our density calculations correspond to 7,900 pairs in Västerbotten County. These results indicate that systematic counts of sap rows can quickly provide credible population density estimates of Eurasian Three-toed Woodpeckers.